'Tomorrow we make it better': an art therapist's reflection on a community mural in a refugee camp in Greece. Issue 4 (2nd October 2019) - Hollingsbee, Emily
ABSTRACT: This paper will explore an art therapist facilitated mural within a refugee camp in Greece. It will present literature regarding a 'psychosocial' frame of art therapy and its considered relevance when working with refugee populations, drawing particular attention to theory on working cross culturally, outside the art therapy room, and the art making process. It will describe the context and present a vignette that reflects on the author's own challenges and discoveries within the mural project that may indicate its significance within the art therapy field. The discussion will explore the possible benefits and value of art mural practice, including thoughts on symbolism within the process and final image. Limitations and further recommendations will be explored and considered. The paper will conclude that a psychosocial approach provides an appropriate framework for art therapists working with refugees and that community murals may hold therapeutic value that could be further explored with primary research and data gathered from participants to expand the discussion of its relevance as a practice within the field. The implications of this paper are that future research into art therapist facilitated community murals is possible within a similar framework and can be used when working with a community of people who have experienced displacement in order to address some of the psychological and social needs. Plain-language summary This paper is an art therapist's reflection on a community mural co-facilitated by a team of art therapists in a refugee camp in Greece. The paper will examine a 'psychosocial' approach within art therapy, whereby the psychological and social needs of a person/s are considered, it will also discuss ideas on working outside the art therapy room and theories relating to the healing elements in a therapeutic art making process. A vignette will describe the personal experiences of an art therapist facilitating a mural within a refugee camp in Greece. The paper will then discuss the possible therapeutic value of the mural, and the benefits of art therapist facilitated community art making that could be drawn from the vignette. The paper will conclude that further research is needed into art therapist facilitated community murals to enhance the discussion and that it would benefit from participant's voices to understand how they experience the practice and to determine any therapeutic value. The paper implies that community murals are a relevant practice to consider within the scope of the art therapy profession and that within a similar framework it can be employed to address the psychological and social needs of a displaced community.